1977
DOI: 10.1177/001391657791003
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Reward Values Associated with Wilderness Use

Abstract: Initially, wilderness users suggested about 30 types of rewards they felt they gained from wilderness experience. Importance ratings suggesting the value of these rewards were obtained from a sample of college students. Individual rewards rated most important were tranquility, natural beauty, and escape from the hectic urban pace. Factoring the importance ratings of the 30 reward items yielded five categories of rewards gained in wilderness which were somewhat similar to those found in previous research: emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 6 publications
0
11
0
3
Order By: Relevance
“…As Bishop et al (2001, p. 119) also recognises "green spaces in a city play an important role in helping residents and visitors to escape temporarily from the crowded streets and buildings: it provides a place to relax". The sense of "escape from the city" has also been found among the most important benefits of wildlife experiences (Rossman and Ulehla, 1977). Furthermore, findings show that the experience of nature in the city is source of a large array of positive feelings to people.…”
Section: Discussion and Recommendationsmentioning
confidence: 94%
“…As Bishop et al (2001, p. 119) also recognises "green spaces in a city play an important role in helping residents and visitors to escape temporarily from the crowded streets and buildings: it provides a place to relax". The sense of "escape from the city" has also been found among the most important benefits of wildlife experiences (Rossman and Ulehla, 1977). Furthermore, findings show that the experience of nature in the city is source of a large array of positive feelings to people.…”
Section: Discussion and Recommendationsmentioning
confidence: 94%
“…Stebbins (1992) found that the reward "Re-Create One's Self" was one of the lowest ranked rewards among barbershop singers. Spirituality was another benefit cited in the field of leisure research (Driver & Bruns, 1999;McDonald & Schreyer, 1991;Rossman & Ulehla, 1977), although it was not mentioned in the reviewed adult music research literature. Although Spirituality was the least agreed upon Personal Benefit in the present study, those who did agree that it existed valued the benefit.…”
Section: Personal Benefitsmentioning
confidence: 99%
“…Further, this area of research relates to important questions in environmental planning and design, including, for instance, visuallandscape assessment, the provision of vegetation and parks in eities, and issues of wilderness management and recreation. Concerning the latter, it appears that aesthetic and emotional experiences are the most important benefits realized by many recreationists in the natural environment (Rossman & Ulehla, 1977;Shafer & Mietz, 1969).…”
Section: Introductionmentioning
confidence: 99%